Gatekeeping, gatewatching, real-time feedback: new challenges for Journalism - Bruns, Axel (Brazilian journalism research, 2015)
How bloggers and other independent online commentators criticise, correct, and otherwise challenge conventional journalism has been known for years, but has yet to be fully accepted by journalists; hostilities between the media establishment and the new generation of citizen journalists continue to flare up from time to time. The old gatekeeping monopoly of the mass media has been challenged by the new practice of gatewatching: by individual bloggers and by communities of commentators which may not report the news first-hand, but curate and evaluate the news and other information provided by official sources, and thus provide an important service. And this now takes place ever more rapidly, almost in real time: using the latest social networks, which disseminate, share, comment, question, and debunk news reports within minutes, and using additional platforms that enable fast and effective ad hoc collaboration between users. When hundreds of volunteers can prove within a few days that a German minister has been guilty of serious plagiarism, when the world first learns of earthquakes and tsunamis via Twitter – how does journalism manage to keep up?
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjUyMDAvYmpyLnYxMG4yLjIwMTQuNzc4